2010
DOI: 10.1074/jbc.m109.075184
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Branched Chain Amino Acid (BCAA) Metabolism Modulates Circulating BCAA Levels

Abstract: Whereas the role of adipose tissue in glucose and lipid homeostasis is widely recognized, its role in systemic protein and amino acid metabolism is less well-appreciated. In vitro and ex vivo experiments suggest that adipose tissue can metabolize substantial amounts of branched chain amino acids (BCAAs). However, the role of adipose tissue in regulating BCAA metabolism in vivo is controversial. Interest in the contribution of adipose tissue to BCAA metabolism has been renewed with recent observations demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
310
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(337 citation statements)
references
References 52 publications
13
310
1
Order By: Relevance
“…Based on whole tissue estimates of BCKD complex activity, WAT leucine kinetics, and BCAA oxidation rates in tissue preparations, WAT could be an important contributor to regulation of whole body BCAA homeostasis (7, 37a, 38, 43). This is supported by a recent study demonstrating that gene expression of BCKD enzyme components was higher in perigonadal WAT compared with gastrocnemius skeletal muscle, and valine oxidation rate was higher in perigonadal WAT compared with gastrocnemius muscle explants (22). In that same study, adipose transplantation experiments demonstrated the potential importance of WAT in modulating systemic BCAA concentrations.…”
supporting
confidence: 76%
“…Based on whole tissue estimates of BCKD complex activity, WAT leucine kinetics, and BCAA oxidation rates in tissue preparations, WAT could be an important contributor to regulation of whole body BCAA homeostasis (7, 37a, 38, 43). This is supported by a recent study demonstrating that gene expression of BCKD enzyme components was higher in perigonadal WAT compared with gastrocnemius skeletal muscle, and valine oxidation rate was higher in perigonadal WAT compared with gastrocnemius muscle explants (22). In that same study, adipose transplantation experiments demonstrated the potential importance of WAT in modulating systemic BCAA concentrations.…”
supporting
confidence: 76%
“…Increased protein consumption containing these essential amino acids may raise their plasma levels, but some data suggest that protein intake and circulating BCAA levels are not necessarily correlated (16,17). Alternatively, downregulation of catabolic enzymes in adipose or other tissues might be involved (8,9). In a parallel study, we analyzed the transcriptome in visceral and subcutaneous adipose tissue samples by RNA sequencing in the cohort of the current study (18).…”
Section: Resultsmentioning
confidence: 99%
“…Why levels of circulating BCAAs are elevated in obesity is unclear. Evidence has been provided for a role of white adipose tissue BCAA metabolism in the modulation of circulating BCAA levels (8,9).…”
mentioning
confidence: 99%
“…Some of the possible mechanisms that have been suggested include reduced activities of key BCAA catabolic enzymes in liver and adipose tissue (27,28) , and differential rates of protein turnover. However, more evidence is required in order to fully understand changes in flux through metabolic pathways that may lead to increased levels of BCAA and related metabolites in insulin resistant individuals.…”
Section: Metabolomicsmentioning
confidence: 99%